Strategi Promosi Dan Alasan MahasiswA Memilih Program Perkuliahan Karyawan Pada Konsultan Perguruan Tinggi (KPT) Di Jakarta - Asriyal Asriyal; Tito Siswanto; Yanti Budiasih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
As a developing country and become one of the most populous countries, Indonesia is considered as a potential market by foreign universities from various parts of the world, both Asian countries, Europe and America who participated in promoting universities in Indonesia on a large scale. This article is written to investigate the promotion and to describe and review the implementation of promotional strategies undertaken by higher education consultant (KPT)in DKI Jakarta. In this study used the analysis of the index technique that describes the respondents on the items of questions posed. Scoring technique used in this research is with a maximum score of 5 and a minimum of 1. Promotional strategies undertaken by the KPT is highly internet marketing based. Internet serve as the main promotional media in addition to other supporting media. Even the use of the internet served as a medium to bring in and also receive the arrival of prospective students.